Pemanfaatan Limbah Plastik dan Oli Bekas untuk Pembuatan Paving Block Ramah Lingkungan - Masry, Rifqa; ., Susilawati; Audina, Windi; Karolina, Josepin; Zahra, Annisa (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
The increase in the volume of plastic waste and used oil in Indonesia has caused serious environmental problems because plastic is difficult to decompose naturally, while used oil is classified as hazardous waste that has the potential to pollute soil and water. Management of these two types of waste is still limited and not yet optimal, so innovations are needed that can reduce the impact of pollution while providing functional added value. This study aims to evaluate the potential use of plastic waste and used oil as mixed materials in the manufacture of environmentally friendly paving blocks and to assess the physical characteristics and initial durability of the resulting products. The research method used is an experiment with an applicative approach. The research was conducted in Pancur Batu District, Deli Serdang Regency, with variations in paving block mixtures including a control mixture, a mixture with the addition of 10% plastic waste from the fine aggregate volume, and a combination of 10% plastic waste and 5% used oil from the cement weight. The manufacturing process included the stages of material preparation, mixing, molding, and drying. Data analysis was performed using quantitative descriptive techniques by comparing the results of physical observations and simple compression tests between mixture variations. The results showed that paving blocks based on plastic waste and used oil had a relatively dense structure, a flat surface, no visible cracks after drying, and were lighter in weight than conventional paving blocks. Based on manual compression tests, the paving blocks were able to support the weight of an adult without initial deformation, making them suitable for use as non-structural lightweight pavement.